Holography, BMN correspondence and deformations - Sousa, Lucas Santos [UNESP] (Universidade Estadual Paulista (Unesp), 2026)
Since the breakthrough paper by Maldacena in the late 90's, the correspondence conjectured between a gravity theory and a field theory has grown so rapidly and so extensively that it has become a research area in its own right. The range of applicability of such a correspondence is now so broad that it spans from cosmological models, describing the evolution of the universe, to non-relativistic condensed matter systems, modeling strongly correlated materials. Among all the known models useful for gravity/gauge duality, particularly interesting are those obtained by deforming existing models, mapping the results from the gravity side to the gauge side or vice-versa. Moreover, deformations serve as powerful tools to better understand how the duality manifests: typically generated by transformations on the supergravity side of the correspondence, these deformations are intrinsically related to energy flows, symmetries of the model, and integrability, and therefore provide results that help us understand how such properties appear in the theory. In this dissertation, we approach this problem by studying different types of deformations, which in general are generated by similar techniques on the supergravity side, often making use of TsT transformations, though not exclusively. For example, we study the beta, gamma, TT, eta, lambda and other deformations, explaining their properties, their conserved quantities, and its gauge/gravity interpretation. We further make use of the BMN mapping/Penrose limit and generalize it to models other than AdS5/CFT4. This procedure consists of mapping a particular sector of the field theory, containing massive operators, to a boosted limit on the gravity side, resulting in a metric that is generally of the pp-wave type, though it can also be a generalization thereof. Moreover, we also investigate the non-commutative properties of this Penrose limit in the presence of deformations. We investigated the noncommutative properties of the Penrose limit in relation to deformations generated by TsT transformations on the supergravity side. We also carried out a bootstrap-type analysis of Leigh--Strassler deformations, obtaining useful insights for future work. Finally, we studied how TsT deformations affect models involving branes and anti-branes that display QCD-like features, such as the presence of mesons and chiral symmetry breaking.

Desde à descoberta por Maldacena no final da década de 90, a correspondência conjecturada entre uma teoria da gravidade e uma teoria de campos cresceu tão rapidamente e de forma tão abrangente que se tornou uma área de pesquisa por si só. A gama de aplicabilidade dessa correspondência é hoje tão ampla que vai desde modelos cosmológicos, que descrevem a evolução do universo, até sistemas de matéria condensada não relativísticos, que modelam materiais fortemente correlacionados. Entre todos os modelos conhecidos e úteis para a dualidade gravidade/gauge, particularmente interessantes são aqueles obtidos por meio de deformações de modelos já existentes, mapeando resultados do lado gravitacional para o lado de gauge ou vice-versa. Além disso, as deformações servem como ferramentas poderosas para compreender melhor como a dualidade se manifesta: tipicamente geradas por transformações no lado da supergravidade da correspondência, essas deformações estão intrinsecamente relacionadas a fluxos de energia, simetrias do modelo e integrabilidade, fornecendo, assim, resultados que nos ajudam a entender como tais propriedades aparecem na teoria. Nesta dissertação abordamos esse problema estudando diferentes tipos de deformações, que em geral são geradas por técnicas similares no lado da supergravidade, frequentemente fazendo uso de transformações TsT, embora não necessariamente. Por exemplo, estudamos as deformações beta, gamma, TT, eta, lambda, dentre outras, explicando suas propriedades, suas quantidades conservadas e como as deformações se manifestam em ambos lados da correspondência. Fazemos ainda uso do mapeamento BMN/limite de Penrose e o generalizamos para modelos além de AdS5/CFT4. Esse procedimento consiste em mapear um setor particular da teoria de campos, contendo operadores massivos, para um limite de impulso no lado gravitacional, resultando em uma métrica que é geralmente do tipo onda plana (pp-wave), embora também possa ser uma generalização desse tipo. Investigamos as propriedades não comutativas do limite de Penrose em relação às deformações geradas por transformações TsT no lado da supergravidade. Também realizamos uma análise do tipo ``bootstrap'' para deformações do tipo Leigh--Strassler, obtendo insights úteis para trabalhos futuros. Por fim, estudamos como as deformações TsT afetam modelos envolvendo branas e anti-branas que exibem características semelhantes às da QCD, como a presença de mésons e a quebra de simetria quiral.
Holografia, correspondência BMN e deformações
Keywords: Holography; Mathematical Physics; Partículas